2019
DOI: 10.1021/acs.iecr.9b02437
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Study on Enhancement of Modulus of Confined Fluid in Nanopores

Abstract: Elastic modulus in fluid is a crucial thermodynamic property due to its close relation to the viscoelastic behaviors in dynamics and the pore size analysis in porous materials. Especially, elasticity in nanoconfined fluid, which exhibits significant deviation from that of bulk fluid, has gained a multitude of applications in industrial and engineering fields. In this work, general expressions of bulk and shear moduli for inhomogeneous fluids have been derived based on Hooke's law. In the bulk phase, the obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 72 publications
4
12
0
Order By: Relevance
“…They found that the elastic modulus has large deviations in the pore from the average value and can have large negative spikes. The negative modulus has been found to relate to the gas-liquid or liquid-solid transitions, which can be stabilized by confinement in nanopores [60]. The calculated average value of the isothermal modulus is consistent with other similar theoretical predictions, and in particular with the data from Dobrzanski et al [62] obtained for argon in silica pores by GCMC using Eq.…”
Section: Local Elastic Propertiessupporting
confidence: 88%
See 3 more Smart Citations
“…They found that the elastic modulus has large deviations in the pore from the average value and can have large negative spikes. The negative modulus has been found to relate to the gas-liquid or liquid-solid transitions, which can be stabilized by confinement in nanopores [60]. The calculated average value of the isothermal modulus is consistent with other similar theoretical predictions, and in particular with the data from Dobrzanski et al [62] obtained for argon in silica pores by GCMC using Eq.…”
Section: Local Elastic Propertiessupporting
confidence: 88%
“…Showing that multiple differing methods of molecular modeling (i.e., MD, GCMC, and DFT) and use of various thermodynamic ensembles are able to predict the same values for the elastic properties of the confined fluid. [44,57,60,162] Note that these theoretical results have practical implications, in particular they suggest the pore-size dependent correction for parameters for the Gassmann equation often used by practitioners. The dependence of fluid compressibility on the pore surface properties could be important for processes such as enhanced oil recovery, or carbon dioxide sequestration, which cause the surface modifications of the geological porous media [172,173].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…It is worth noting that a recent work showed that the average of the local moduli of confined liquid argon calculated using cDFT matches the elastic moduli calculated from the GCMC simulations using eq 4. 93 Although the agreement between the predictions for the elastic modulus from molecular simulation and from EOS is only qualitative, it is still an important milestone. The lack of quantitative agreement is not unexpected; the primary reason for the deviation may be the difference of fluid−fluid and solid−fluid interaction potentials.…”
Section: ■ Discussionmentioning
confidence: 99%